Charge‐Segregated Stacking Structure with Anisotropic Electric Conductivity in NIR‐Absorbing and Emitting Positively Charged π‐Electronic Systems. (17th January 2023) - Yamasumi, Kazuhisa; Ueda, Kentaro; Haketa, Yohei; Hattori, Yusuke; Suda, Masayuki; Seki, Shu; Sakai, Hayato; Hasobe, Taku; Ikemura, Ryoya; Imai, Yoshitane; Ishibashi, Yukihide; Asahi, Tsuyoshi; et al.
Abstract: Squarylium‐based π‐electronic cation with an augmented dipole was synthesized by methylation of zwitterionic squarylium. The cation formed various ion pairs in combination with anions, and the ion pairs exhibited distinct photophysical properties in the dispersed state, ascribed to the formation of J‐ and H‐aggregates. The ion pairs provided solid‐state assemblies based on cation stacking. It is noteworthy that complete segregation of cations and anions was observed in a pseudo‐polymorph of the ion pair with pentacyanocyclopentadienide as a π‐electronic anion. In the crystalline state, the ion pairs exhibited photophysical properties and electric conductivity derived from cation stacking. In particular, the charge‐segregated ion‐pairing assembly induces an electric conductive pathway along the stacking axis. The charge‐segregated mode and fascinating properties were derived from the reduced electrostatic repulsion between adjacent π‐electronic cations via dipole–dipole interactions. Abstract : Ordered arrangements and resulting anion‐dependent photophysical properties were observed in the dispersed and solid‐state ion pairs of squarylium‐based π‐electronic cation with an augmented dipole. A completely charge‐segregated assembly was formed in the ion pair with a π‐electronic anion, exhibiting solid‐state photophysical properties and anisotropic electric conductivity according to the stacking structure.